THE METHOD OF COMMITTING CRIME AS NECESSARY ELEMENT OF CORPUS DELICTI - Khurramovich, Khudaykulov Feruzbek (International Journal of Business, Law and Political Science, 2024)
The article widely uses logical, inductive, deductive, systematic, logical-legal, comparative-legal research methods. In particular, among the signs of the objective side of the crime, the method of committing the crime has its own importance, and any crime is committed in a certain way. The method of committing a crime is a form of external expression of a socially dangerous act, and in most cases, the legislator considers the method as a necessary or aggravating sign of the crime in the criminal legislation. The analysis of the articles of the Special part Criminal Code shows that the method of committing a crime is expressed by the legislator in two forms in the criminal law. The first is as a form of a socially dangerous act, while the second is considered independently. As an example of the first, articles 110, 118, 119, 164 of the Criminal Code can be given. In the disposition of these articles, words such as "torture", "killing or threatening with the use of force", "use of force", "intimidation with the use of force" represent the method of committing the crime. As an example of the latter, articles 166, 168 and 169 can be cited. At the same time, the doctrine of criminal law and existing scientific research were analyzed, and reasonable theoretical recommendations were developed in this regard. At the same time, the theoretical and practical problems related to the method of committing crime and its types were highlighted, and the results of the survey on the introduction of the norm related to the structure of the crime into the criminal legislation were reflected, and in this regard, specific proposals and recommendations were developed for improving the criminal legislation of the Republic of Uzbekistan.